Associations between sex-typed behaviour at age 3½ and levels and patterns of physical activity at age 12: the Avon Longitudinal Study of Parents and Children. Issue 7 (26th May 2010) - Mattocks, Calum; Hines, Melissa; Ness, Andy; Leary, Sam; Griffiths, Alex; Tilling, Kate; Blair, Steven N; Riddoch, Chris
Abstract : Background: Differences in sex-typed behaviour, including physical activity, are already apparent among preschool children. Purpose: To examine the associations between early sex-typed behaviour and later physical activity. Methods: Children from the Avon Longitudinal Study of Parents and Children were asked to wear an accelerometer for 7 days at age 12. Physical activity outcomes were counts per minute (counts/min) and minutes of moderate to vigorous physical activity (MVPA). Sex-typed behaviour was assessed using the Pre-School Activities Inventory (PSAI) at age 3½. Multivariable regression was used to examine the association between PSAI and physical activity, separately for boys and girls. Results: Accelerometer data were collected from 2593 boys and 2858 girls, mean (SD) age 11.8 (0.23) years. A one point higher PSAI score (mean (SD) 61.7 (8.7) and 37.0 (9.1) for boys and girls, respectively) was associated with a higher level of physical activity (counts/min) of 2.3 (95% CI 0.9 to 3.7) in boys and 0.7 (95% CI −0.1 to 1.4) in girls. This is equivalent to a higher counts/min of 56.7 (95% CI 23.1 to 90.3) and 16.6 (95% CI −2.4 to 35.5) for boys and girls, respectively, for a higher PSAI score equivalent to the difference between boys and girls (24.7). Results for MVPA were similar. Conclusions: Higher male-typical behaviour in early childhood is associated with higher physical activity in early adolescence, particularly in boys.